Test Antibacterial Activity from Ashitaba Stem Ethanol Extract (Angelica keiskei (Miq.) Koidz) Against Streptococcus mutans ATCC 25175 - Luluk Aniqoh Meliana Putri (Universitas STRADA Indonesia, 2022)
Ashitaba stems contain chemical compounds such as alkaloids, tannins, flavonoids and saponins. This study aimed to determine the antibacterial activity of ashitaba stem extract against Streptococcus mutans ATCC 25175. Ashitaba stem powder was extracted by maceration method with 96% ethanol solvent. The extract obtained was tested for antibacterial activity against Streptococcus mutans ATCC 25175 using the diffusion method with concentrations of 50%, 25%, 12.5% ​​and 6.25% to determine the concentration of the most active extract. The most active extract was known from the diameter of the inhibition zone which had the greatest value. The results showed that the ashitaba stem extract had antibacterial activity against Streptococcus mutans ATCC 25175. The 50% concentration of the ashitaba stem extract had an average inhibitory diameter of 18 mm which was the most active concentration of the ashitaba stem extract, the 25% concentration of the ashitaba stem extract had an average The average inhibitory diameter was 16.5 mm, the concentration of 12.5% ​​of the ashitaba stem extract had an average inhibitory diameter of 14.8 mm, the concentration of 6.25% of the ashitaba stem extract had an average inhibitory diameter of 12.5 mm.